Maritime Boundaries - Beazley, P. B. (The International Hydrographic Review, 2015)
A brief historical background to maritime boundary delimitation; the effect o f the introduction of maritime zones of jurisdiction extending to considerable distances offshore, and the development of the principles governing modern offshore boundary determination; a discussion of some of the theoretical and practical problems that have arisen.